Efektivitas Model Pembelajaran Teams Games Tournament (TGT) Berbantuan Media 3D MatchJU Dalam Meningkatkan Hasil Belajar Siswa - Kamal Ramadhani; Jarot Tri Bowo Santoso (Jurnal Pendidikan Ekonomi (JUPE), 2025)
Accounting material is often an obstacle for high school students because this material requires strong calculation and analysis, including at MA Al Huda Kedu.  For this reason, it is necessary to have learning innovations carried out by teachers, one of which can be used is the Teams Games Tournament (TGT) learning model assisted by 3D MatchJU in improving student learning outcomes. This study used a quantitative approach with a one group pretest posttest research design with a population of 32 students. The sample was taken using saturated sampling technique, but the data obtained were only 21 students. Data analysis was carried out using the Wilcoxon test and the N-Gain test. The results showed that there was a difference in the average student learning outcomes before and after the TGT model treatment assisted by 3D MatchJU media. In addition, the use of TGT model assisted by 3D MatchJU media is effective in improving learning outcomes in the medium effectiveness category. This study implies that the use of non-digital physical media, such as 3D MatchJU can be used to improve students' accounting skills.